Upaya untuk Meningkatkan Potensi Objek Wisata di Kota Banjarmasin (Studi pada Wisata Susur Sungai) - Febrian, Ferry; Suherty, Lina (PPJP ULM, 2023)
The study aims to discover obstacles and efforts to increase the potential of tourist attractions in Banjarmasin City. This research uses qualitative methods with a case study approach. Techniques for collecting data are observation, structured interviews, and documentation of related sources. The study results stated that the leading tourist attraction was centered on the riverbank. Several obstacles hindered the riverside tourist attraction regarding training, structuring traders, the Covid-19 pandemic, limited budget, natural factors, and limited information. Efforts to develop tourist attractions along the river, improve infrastructure, and carry out promotions through the Android application Nagabungas, which can be downloaded from the Play Store. It can restore the riverbank area to improve river ecology, restore the function of the riverbank as a public area, restore historical riverbank areas, restore riverbank heritage objects, and enhance the economy of riverbank communities.